2020
DOI: 10.1016/j.ymthe.2019.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Rescue from Stx2-Producing E. coli-Associated Encephalopathy by Intravenous Injection of Muse Cells in NOD-SCID Mice

Abstract: Shiga toxin-producing Escherichia coli (STEC) causes hemorrhagic colitis, hemolytic uremic syndrome, and acute encephalopathies that may lead to sudden death or severe neurologic sequelae. Current treatments, including immunoglobulin G (IgG) immunoadsorption, plasma exchange, steroid pulse therapy, and the monoclonal antibody eculizumab, have limited effects against the severe neurologic sequelae. Multilineage-differentiating stress-enduring (Muse) cells are endogenous reparative non-tumorigenic stem cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Human Muse cells were used to rescue a NOD-SCID mouse model of EHEC (VT2) induced neurological disease (Ozuru et al, 2019). Forty eight hour after gastrointestinal EHEC treatment Muse cell i.v.…”
Section: Stem Cellsmentioning
confidence: 99%
“…Human Muse cells were used to rescue a NOD-SCID mouse model of EHEC (VT2) induced neurological disease (Ozuru et al, 2019). Forty eight hour after gastrointestinal EHEC treatment Muse cell i.v.…”
Section: Stem Cellsmentioning
confidence: 99%
“…Muse cell-derived neuronal cells incorporate into the pyramidal tract, including the pyramidal decussation, as demonstrated by anterograde and retrograde tracing, and into the sensory tract, as demonstrated by somatosensory-evoked potentials and the formation of synapses with host neuronal cells at 3 months, leading to statistically meaningful functional recovery [ 34 , 38 ]. Spontaneous differentiation of Muse cells into neuronal and glial cells after homing to the damaged central nervous system is also reported in other models, perinatal hypoxic ischemic encephalopathy, brain hemorrhage, ALS, and STEC-related encephalopathy [ 36 , 37 , 39 , 40 ]. In an acute myocardial infarction model, Muse cells homed to the post-infarct tissue and within 2 weeks spontaneously differentiated into cells positive for cardiomyocyte markers, such as troponin-I, sarcomeric α-actinin, and connexin 43, exhibiting calcium influx and efflux synchronous with heart activity recorded by an electrocardiogram [ 6 ].…”
Section: Basic Characteristics Of Muse Cellsmentioning
confidence: 62%
“…In a rabbit acute myocardial infarction model, ~14.5% of intravenously injected Muse cells engrafted into the post-infarct heart at 3 days, whereas only a few or no MSCs integrated into the heart in the same model [ 6 ] ( Figure 6 ). In mouse models of epidermolysis bullosa [ 33 ], lacunar stroke l [ 34 ], doxorubicin-induced nephropathy [ 35 ], ALS [ 36 ], and Shiga toxin-producing Escherichia coli (STEC)-associated encephalopathy [ 37 ], as well as in rat models of middle cerebral artery occlusion ischemia and perinatal hypoxic ischemic encephalopathy [ 38 , 39 ], Muse cells exhibited superiority over MSCs/non-Muse MSCs in selective homing to the sites of damage. Not only in these animal models, but also the data collected from patients with stroke and acute myocardial infarction demonstrated that an increase in the serum S1P level precedes the increase in the number of circulating endogenous Muse cells after the cell injury onset [ 3 , 7 ].…”
Section: Basic Characteristics Of Muse Cellsmentioning
confidence: 99%
See 2 more Smart Citations